2017
DOI: 10.1038/s41467-017-01138-7
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Weyl semimetals and low-dissipation magnetization control in insulators by spin–orbit torques

Abstract: Reliable and energy-efficient magnetization switching by electrically induced spin-orbit torques is of crucial technological relevance for spintronic devices implementing memory and logic functionality. Here we predict that the strength of spin-orbit torques and the Dzyaloshinskii-Moriya interaction in topologically nontrivial magnetic insulators can exceed by far that of conventional metals. In analogy to the quantum anomalous Hall effect, we explain this extraordinary response in the absence of longitudinal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 58 publications
3
67
0
1
Order By: Relevance
“…The corresponding topological phase diagram is depicted in Figure 6. We note that the overall situation is somewhat reminiscent to that predicted for a Bi bilayer where magnetization rotation induced by the spin-orbit torque forces the topological phase transition [36].…”
Section: E Topological Phases Across a Domain Wallmentioning
confidence: 67%
See 1 more Smart Citation
“…The corresponding topological phase diagram is depicted in Figure 6. We note that the overall situation is somewhat reminiscent to that predicted for a Bi bilayer where magnetization rotation induced by the spin-orbit torque forces the topological phase transition [36].…”
Section: E Topological Phases Across a Domain Wallmentioning
confidence: 67%
“…To provide more insight into the proximity effect on the electronic band structure of graphene and to analyze its quantum transport behavior, we build a model tight-binding Hamiltonian as follows [31,[36][37][38][39]…”
Section: B Tight-binding Modelmentioning
confidence: 99%
“…While magnets have been successfully fabricated in 2D 32,33 , combining 2D magnetism with non-trivial topological proper-ties holds great opportunities for topological transport phenomena and technological applications in magneto-electric, magneto-optic, and topological spintronics [34][35][36][37] . As a consequence, studying the unique interplay of topological phases with the dynamic magnetization of solids currently matures into a significant burgeoning research field of condensedmatter physics (see, e.g., Refs.…”
mentioning
confidence: 99%
“…As a consequence, studying the unique interplay of topological phases with the dynamic magnetization of solids currently matures into a significant burgeoning research field of condensedmatter physics (see, e.g., Refs. [37][38][39][40][41][42]. In this context, for example, magnetic interfaces with topological insulators 43 and layered van der Waals crystals [44][45][46] , which can exhibit ferromagnetism at room temperature, constitute compelling and experimentally feasible classes of 2D quantum materials.…”
mentioning
confidence: 99%
“…Combining the Dresselhaus [001] SOC, exchange coupling, and spin-dependent effective mass, it will be shown that such a 2DES is a Chern insulator which shows the QAH effect. Meanwhile, inspired by recent spintronic research [28,29], the topological phase transitions will be induced by tuning the magnetization orientation (figure 1(b)), which is more practical than traditionally manipulating the exchange coupling strength which is no longer a tunable parameter after the fabrication of the system.…”
Section: Introductionmentioning
confidence: 99%